2020
DOI: 10.1001/jamaoto.2019.2663
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of Patients With Ménière Disease in Ethiopia, India, and the United States

Abstract: Classic Ménière disease is easily identified by the experienced otologist. 1 But how do patients feel about their disease? Surprisingly, patients with Ménière disease whose vestibular symptoms were reduced or eliminated in a recent study did not rate their overall condition as improved. 2 Herein we report a survey of a convenience sample of patients with Ménière disease in Ethiopia, India, and the United States to assess their concerns associated with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Similar to what Lee et al found in their study, it was recognized that there is a gap in understanding of the patient perspective in head and neck cancer care. Specifically, is the perspective of patients with head and neck cancer different from the physician perspective?…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Similar to what Lee et al found in their study, it was recognized that there is a gap in understanding of the patient perspective in head and neck cancer care. Specifically, is the perspective of patients with head and neck cancer different from the physician perspective?…”
supporting
confidence: 82%
“…This small, limited study highlights that the patient perspective differs from the physician perspective. Patient treatment goals may be different from the physician treatment goals.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Bilateral SNHL is a major issue for patients with MD, since it has a significant impact on the health-related quality of life (Lopez-Escamez et al 2009; Levo et al 2012). Half of the patients report they are no longer the same person owing to their hearing loss and that they live in fear of another episode (Lee et al 2020). In this study, we have identified clinical predictors to develop SNHL in the contralateral ear, and we have built a predictive model to assess the risk of bilateral SNHL.…”
Section: Discussionmentioning
confidence: 99%